Kebertahanan Mbaru Gendang (Rumah Adat) Pada Masyarakat Manggarai di Desa Ketang Kecamatan Lelak, Kabupaten Manggarai, Flores Nusa Tenggara Timur - Sanul, Selviana; Aditya, I Gst. Ngr. A. Krisna; Mahadewi, Ni Made Anggita Sastri (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
For the Manggarai people in Ketang Village, Mbaru Gendang have a crucial role and strategic function for the continued existence of their culture. This house has deep significance and meaning for the soul and life of the Manggarai people and culture. Mbaru Gendang provides physical, psychological and spiritual comfort for its residents. In the midst of the increasingly rapid development of globalization, culture has also changed with the times. However, until now the people of Ketang Village still maintain their customs, namely mbaru gendang. This research aims to explain the factors of survival of the mbaru gendang in and explore the symbolic meaning of the mbaru gendang in the Ketang Village community. This research uses the theory of Semiotics Theory: Roland Barthez. The concepts used as guidelines in this research are survival, traditional houses, mbaru gendang, and symbolic meaning. This research uses qualitative research methods through observation, interviews and literature study techniques. The researcher is the main research instrument, assisted by interview guides, voice recorders, cameras and writing tools. The results of the research show that the survival factor of mbaru gendang is the function factor of mbaru gendang, namely, mbaru gendang as a place to live, or for family gatherings, mbaru gendang bate mbaru (as a shelter), mbaru gendang as a place to receive guests, mbaru gendang as a place for lonto leok (meetings). (customary assembly), mbaru gendang as a place where the spirits of ancestors reside, mbaru gendang bate kuni agu if (as an identity) for the Manggarai people in Ketang Village. Mbaru gendang basically contains many symbols that describe the identity of the Manggarai people and culture of the Ketang Village community. Its round shape is a symbol of a mindset and lifestyle that prioritizes unity and togetherness.